Hubungan Antara Kemandirian Belajar dan Kepercayaan Diri dengan Adversity Quotient pada Siswa di SMP Negeri 2 Kragan - Rizqiatul Fithriyyah; Dhini Rama Dhania (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the relationship between learning independence and self-confidence with the Adversity Quotient (AQ) in students at SMP Negeri 2 Kragan. The research method used is quantitative by collecting data through a measurement scale. The results of the analysis show that there is a very significant relationship between learning independence and self-confidence and the Adversity Quotient, with a correlation coefficient of 0.560 and a significance level of 0.000 (p<0.01). The contribution of learning independence and self-confidence to the Adversity Quotient was 31.4%, while 68.6% was influenced by other factors not researched. This research emphasizes the importance of developing students' learning independence and self-confidence to increase their fighting power in facing various academic challenges.